Efficacy of foliar application of Chlorella vulgaris extract on chemical composition and biological activities of the essential oil of spearmint (Mentha spicata L.) - Fatemeh Jamshidi-Kia; Keramatolah Saeidi; Zahra Lorigooini; Bahram Hosseinzadeh Samani (Heliyon)
The microalgal have an essential role in agriculture, where they are used as biofertilizers. This study aimed to determine the effect of C. vulgaris extract on the chemical composition and biological activities of the Essential Oil (EO) of Mentha spicata. The extract of C. vulgaris was prepared and applied at three different concentrations (50, 75, and 100 %). The EOs of M. spicata were analyzed by gas chromatography-mass spectrometry (GC-MS). The DPPH radical scavenging capability and Ferric Reducing Antioxidant Power (FRAP) techniques were used to assess the antioxidant activity of EOs. The antimicrobial activity of EO was evaluated using the microdilution method against Staphylococcus aureus. The results of GC-MS analysis of EOs identified 46 components, with Carvone (77.5–65.4 %), Limonene (10.31–6.9 %), β-elemene (1.56–0.98 %), and Caryophyllene (10.92–4.77 %) being the predominant constituents. From the highest concentration ranged from 100 % C. vulgaris extract to control respectively, yield and EO content ranged from 171.24 to 131.74 g/m2 and 0.34 to 0.18 %, respectively; Antioxidant activity by DPPH and FRAP methods varied from 1.56 to 4.45 mg/mL, and 405.63 to 68.68 μMFe2+/g, respectively; the Minimum Inhibitory Concentrations (MIC) ranged from 2.4 to 9.6 mg/mL in various treatments. The results indicated that the C. vulgaris extract significantly increased the yield, EO%, Carvone, Limonene, and antioxidant and antibacterial activities compared to the control. The extract of C. vulgaris showed promise as a biofertilizer to enhance the yield, chemical composition, and biological activities of M. spicata.